MicroRNA-128b mediates lipopolysaccharide-induced apoptosis via reactive oxygen species in human pulmonary microvascular endothelial cells (Clinics, 2022)
Objectives: This study aimed to explore the effects of miR-128b in the regulation of Lipopolysaccharide (LPS) induced apoptosis.Methods: Human Pulmonary Microvascular Endothelial Cells (HPMECs) were transfected with an miR-128b inhibitor and stimulated with LPS for 24 h. FCM was performed to detect apoptosis and Reactive Oxygen Species (ROS) production. In addition, miRNA and caspase-3 expression levels were determined using real-time quantitative polymerase chain reaction and western blotting.Results: LPS significantly induced apoptosis and ROS production and upregulated miR-128b and caspase-3 expressions in HPMECs. However, LPS-induced effects were suppressed when an miR-128b inhibitor was used. Preincubation with NAC decreased the LPS-induced apoptosis of HPMECs.Conclusions: These effects were mediated by miR-128b via the caspase-3 pathway.